Effect of different turbulence models on combustion and emission characteristics of hydrogen/air flames. (5th October 2017) - Yilmaz, Harun; Cam, Omer; Tangoz, Selim; Yilmaz, Ilker
Abstract: This paper aims to present modeling results of hydrogen/air combustion in a micro-cylindrical combustor. Modeling studies were carried out with different turbulence models to evaluate performance of these models in micro combustion simulations by using a commercially available computational fluid dynamics code. Turbulence models implemented in this study are Standard k-ε, Renormalization Group k-ε, Realizable k-ε, and Reynolds Stress Transport. A three-dimensional micro combustor model was built to investigate impact of various turbulence models on combustion and emission behavior of studied hydrogen/air flames. Performance evaluation of these models was executed by examining combustor outer wall temperature distribution; combustor centerline temperature, velocity, pressure, species and NOx profiles. Combustion reaction scheme with 9 species and 19 steps was modeled using Eddy Dissipation Concept model. Results obtained from this study were validated with published experimental data. Numerical results showed that two equation turbulence models give consistent simulation results with published experimental data by means of trend and value. Renormalization Group k-ε model was found to give consistent simulation results with experimental data, whereas Reynolds Stress Model was failed to predict detailed features of combustion process. Highlights: Simulating multistep hydrogen/air combustion in a micro combustor. Varying turbulence model during simulations. Assessing relative performance of turbulence models. Finding the most appropriate turbulence model for micro combustion simulations.